2010
DOI: 10.1002/ejic.201000405
|View full text |Cite
|
Sign up to set email alerts
|

5‐(2‐Thienyl)tetrazolates as Ligands for RuII–Polypyridyl Complexes: Synthesis, Electrochemistry and Photophysical Properties

Abstract: In this contribution, we report the synthesis, the characterization and the study of the electrochemical and photophysical properties of some novel mononuclear Ru II -polypyridyl complexes of the general formula [Ru(tpy)(bpy)L] + (tpy = 2,2Ј:6Ј,2"-terpyridine, bpy = 2,2Ј-bipyridyl) in which L is represented by 5-(2-thienyl)tetrazolate-type ligands. In addition, the reactivity of these mononuclear species toward different electrophiles such as H + and CH 3 + has been investigated, and the effects of the resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Intermediates 1, 3, and 8 were synthesized following literature procedures. 51,52 Intermediates 2, 4, and 9, although reported in the literature, [53][54][55] were synthesized following modified routes. For the synthesis of PH targets, intermediates 12 and 14 were synthesized following literature procedures, with modifications.…”
Section: Resultsmentioning
confidence: 99%
“…Intermediates 1, 3, and 8 were synthesized following literature procedures. 51,52 Intermediates 2, 4, and 9, although reported in the literature, [53][54][55] were synthesized following modified routes. For the synthesis of PH targets, intermediates 12 and 14 were synthesized following literature procedures, with modifications.…”
Section: Resultsmentioning
confidence: 99%
“…The Ru­(PTA) complexes emit in the yellow-red region of the electromagnetic spectrum at room temperature, with the maximum photoluminescence (PL) wavelength (λ max ) in the 560–615 nm region. In all Ru­(PTA) cases, the PL emission originates from 3 MLCT states involving the charge transfer from polypyridyl and tetrazole ligands to t 2g of the ruthenium center, as demonstrated by the shape and position of the emission band in the 550–700 nm region, and by the lifetime values, which are in the expected range for Ru–tetrazole complexes, e.g., 100–500 ns in degassed acetonitrile . The PL emission quantum yields are calculated by comparison with the known [Ru­(bpy) 3 ] 2+ one (Φ std = 9.5%) in acetonitrile solution at room temperature with an excitation wavelength of 405 nm (see Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“… a Complex 7 is obtained from neutral RuTz [Ru­(phen) 2 (TzBA) 2 ] at 20 or 16 V . fwhm = full width at half-maximum. b At 20 V. c At 16 V. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diaz et al [38] reported a strong absorption at 350 nm for terthiophene and, if these absorptions are compared, it is possible to see how the inclusion of terthiophene into the structure of a ruthenium complex may be generating the overlapping absorption spectrum of terthiophene and, in turn, a shift for both 1 and 2, the latter being higher in energy, probably due to the presence of methyl groups on complex 2 and, therefore, the formation of a complex bearing a more positive charge. This may justify the slight shift of one band relative to the other in the near UV spectrum [25,39]. The molar absorptivity (e) recorded for complexes 1 and 2 was 1.1 Â 10 4 and 1.7 Â 10 4 molÁL À1 Ácm À1 , respectively.…”
Section: Characterization By Uv-vis Spectroscopymentioning
confidence: 94%